Design method of asphalt mixture, noise reduction asphalt preparation method, system and application

Through the design method, the aggregate particle size and void ratio of the asphalt mixture are controlled, and combined with the oil film thickness, the noise reduction, anti-slip and crack resistance of the asphalt mixture are achieved, and the problem of single performance in the prior art is solved.

CN119294094AActive Publication Date: 2025-01-10CENT FORTUNE CREATION TECH GRP CO LTD +2

Patent Information

Application Number
CN202411411064.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

Existing asphalt mixtures are difficult to combine noise reduction and other properties, such as anti-slip properties, crack resistance and durability in use.

Method used

The maximum particle size of the aggregate is controlled by design method, and the noise reduction ability of the asphalt mixture is separated from the coarse aggregate and fine aggregate, the aggregate closest to the design target void ratio is obtained as the design grading of asphalt, and as planned The thickness of the oil film exerts the best noise reduction performance.

Benefits of technology

It realizes asphalt mixture that takes into account anti-slip performance, crack resistance and durability, improves noise reduction effect, and solves the problem of single performance in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119294094A_ABST
    Figure CN119294094A_ABST
Patent Text Reader

Abstract

The invention discloses a design method of an asphalt mixture, a noise-reducing asphalt preparation method, a system and application. The design method comprises the steps that skeleton gap type diabase is selected as stone, and the particle size distribution range of the stone is at least two grades of gradation of 0-n1 and n2-n3; other gradations except 0-n1 in the stone are used as coarse aggregates; measuring the synthetic compact density and the synthetic gross volume relative density of the coarse aggregate, and calculating the void rate of the coarse aggregate; calculating the use amount of the mineral powder to be supplemented and the target void ratio; calculating to obtain the ratio of the coarse aggregate to the fine aggregate; obtaining new fine aggregates and new coarse aggregates based on the particle size distribution range of the medium aggregates; drawing up the oil film thickness h, calculating the specific surface area A of the aggregate, and then calculating the amount of asphalt; calculating respective asphalt-aggregate ratios, and selecting design gradation according to the void ratio; and preparing the asphalt mixture according to the designed gradation. According to the scheme, the problems that existing asphalt is single in performance and difficult to have noise reduction performance and other performance at the same time are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of asphalt, and in particular to a design method for an asphalt mixture, a preparation method for noise-reducing asphalt, a system and uses thereof. Background Art

[0002] With the annual growth of the number of cars in my country, the contradiction between road noise pollution and the demand for traffic development has become increasingly prominent. Compared with traditional passive noise reduction methods such as building road sound barriers, active noise reduction on the road surface refers to a technical method of targeted design of asphalt mixture to suppress and absorb road / tire contact noise. Compared with passive noise reduction, active noise reduction can achieve synchronous noise reduction inside and outside the car, which can not only reduce the interference with the daily life of residents along the line, but also improve the comfort of driving and riding. Active noise reduction aims to suppress the source of noise, and has more advantages than passive noise reduction in many aspects such as saving noise pollution control costs and beautifying urban landscapes. Among the existing various low-noise pavement technical solutions, on the one hand, most of them have poor noise reduction effects, and the existing low-noise pavement technology still has some limitations, such as limited noise reduction effects and short duration of noise reduction effects; on the other hand, it is also necessary to consider improving the noise reduction effect while retaining other properties of asphalt, such as anti-skid performance, anti-cracking performance, and durability of use. Therefore, the existing asphalt has a single performance and it is difficult to have both noise reduction performance and other performance problems. Summary of the invention

[0003] The purpose of the present invention is to propose a design method for asphalt mixture, which controls the maximum particle size of aggregate during the preparation process, separates the noise reduction ability of the asphalt mixture from the coarse aggregate and the fine aggregate, obtains the aggregate closest to the designed target void ratio as the design gradation of asphalt, and then exerts the best noise reduction performance of asphalt according to the proposed oil film thickness.

[0004] The present invention also provides a method for preparing noise-reducing asphalt. When the asphalt is prepared by designing the gradation according to the above-mentioned design method, an asphalt mixture having both anti-skid performance, anti-cracking performance and durability can be obtained.

[0005] The present invention also provides a noise reduction asphalt, which is prepared by the above-mentioned method for preparing the noise reduction asphalt.

[0006] The invention also proposes a use of an asphalt mixture in preparing noise-reducing asphalt.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] A method for designing an asphalt mixture comprises the following steps:

[0009] (1) Select skeleton-voided diabase as the stone material, and the particle size distribution range of the stone material is at least two levels of 0-n1 and n2-n3; 0<n1≤3≤n2<n3≤14mm; n1, n2 and n3 represent the particle size respectively;

[0010] (2) Use the other gradations other than 0-n1 in the stone as coarse aggregate; measure the synthetic compact density γ of the coarse aggregate s and synthetic wool volume relative density γ b , calculate the void ratio VCA of coarse aggregate DRC ;

[0011] VCA DRC =(1-γ s / γ b )×100%;

[0012] (3) Take the 0-n1 grade in the stone as fine aggregate; design the amount of mineral powder to be added q p and the target porosity V of asphalt v ; The coarse aggregate, fine aggregate and mineral powder meet the following requirements:

[0013] q c +q f +q p =100%;

[0014]

[0015] q c is the mass percentage of coarse aggregate, q f is the mass percentage of fine aggregate, q p is the mass percentage of mineral powder; q a V is the empirical value of oil-stone ratio; v is the target void ratio; γ f is the apparent relative density of fine aggregate, γ p is the apparent relative density of the mineral powder; γ a is the relative density of asphalt;

[0016] (4) Calculate the ratio of coarse aggregate to fine aggregate as q c :q f ;

[0017] (5) q calculated according to step (4) c :q f Made into medium aggregate; based on the particle size distribution range of the medium aggregate, increase the passing rate of the sieve hole z to obtain new fine aggregate, and reduce the passing rate of the sieve hole z to obtain new coarse aggregate; 0<z<n1;

[0018] (6) Determine the oil film thickness h, calculate the aggregate specific surface area A of the new fine aggregate, new coarse aggregate and medium aggregate of the corresponding gradation, and then calculate the asphalt dosage P of medium aggregate, fine aggregate and coarse aggregate respectively by the following formula: b :

[0019] Asphalt dosage P b = oil film thickness h × aggregate specific surface area A;

[0020] (7) The asphalt dosage P corresponding to the medium aggregate, fine aggregate and coarse aggregate b Calculate the oil-stone ratio of each, calculate the actual porosity of each by volume method according to the oil-stone ratio of each, and compare the actual porosity with the porosity V designed in step (3) v By comparison, select the medium aggregate, fine aggregate or coarse aggregate with the closest void ratio as the design gradation of asphalt mixture.

[0021] (8) Obtain the designed gradation for preparing the asphalt mixture according to step (7).

[0022] Preferably, before step (1), the properties of the asphalt are associated with the particle size range of the stone, and parameter requirements are set for particles in each particle size range;

[0023] In the step (1), when selecting stones, the particles corresponding to the selected stones in different particle size ranges are compared with the parameter requirements to ensure that the particles meet the parameter requirements.

[0024] It can be optimized that in the step (1), when selecting stones, the parameter requirements of the coarse aggregate and the fine aggregate of the stones are compared respectively;

[0025] The parameters required for the comparison of coarse aggregate include: polishing value, crushing value, Los Angeles abrasion value, water absorption rate, needle-like particle content, mud content, weak particle content and one or more of the following: adhesion to modified asphalt;

[0026] The parameter requirements for comparing fine aggregate include one or more of: solidity, sand equivalent and apparent relative density.

[0027] It can be optimized that in the step (1): when selecting stones, the particle size distribution range of the stones is 0-n1, n2-n3 and n4-n5; 0<n1≤3≤n2<n3≤n4<n5≤14mm; n3, n4 and n5 represent the particle size respectively;

[0028] In step (2), the particles n2-n3 and the particles n4-n5 are mixed in a specific ratio, and then the synthetic compact density γ of the coarse aggregate is measured. s and synthetic wool volume relative density γ b .

[0029] Optimally, the particle size distribution range of the diabase is 0-3mm and 3-5mm in two-grade distribution, or 0-3mm, 3-5mm and 5-8mm in three-grade distribution, or 0-3mm and 5-10mm in two-grade distribution;

[0030] In the step (1), n1 is 3 mm; the maximum particle size of the stone is less than 13.2 mm; and the sieve hole diameter z is 2.36 mm;

[0031] In the step (6), the thickness of the oil film is set to be 15-17 μm.

[0032] It can be optimized that between step (7) and step (8), the oil-rock ratio range is determined according to the leakage loss and scattering loss tests, the oil-rock ratio corresponding to the intersection of the inflection point tangent of the leakage loss curve is the maximum oil-rock ratio, the oil-rock ratio corresponding to the intersection of the inflection point tangent of the scattering loss curve is the minimum oil-rock ratio, the minimum oil-rock ratio and the maximum oil-rock ratio form an optional oil-rock ratio range, the oil-rock ratio is selected within the optional oil-rock ratio range and asphalt is prepared according to the design grade, and the designed oil-rock ratio is selected according to the porosity of the asphalt;

[0033] In the step (8), the designed gradation and designed asphalt-to-stone ratio for preparing the asphalt mixture are obtained.

[0034] A method for preparing noise-reducing asphalt, using the above-mentioned method for designing an asphalt mixture, and preparing an asphalt mixture according to the design result of step (8).

[0035] A noise reduction asphalt, comprising: an asphalt mixture;

[0036] The asphalt mixture is prepared by the above-mentioned method for preparing noise-reducing asphalt.

[0037] An asphalt mixture design system, used to execute the above-mentioned asphalt mixture design method, comprising: a material selection module, an aggregate calculation module, and a material calculation module;

[0038] The material selection module is used to perform the step (1);

[0039] The aggregate calculation module is used to execute steps (2)-(5);

[0040] The material calculation module is used to execute steps (6)-(8).

[0041] A use of an asphalt mixture in preparing noise-reducing asphalt, wherein the design gradation and the design asphalt-stone ratio of the asphalt mixture are designed according to the above-mentioned design method for an asphalt mixture.

[0042] Compared with the prior art, one of the above technical solutions has the following beneficial effects:

[0043] The present invention provides a method for preparing noise-reducing asphalt, which controls the maximum aggregate particle size during the preparation process, separates the noise reduction ability of the asphalt mixture from the coarse aggregate and the fine aggregate, obtains the aggregate closest to the designed target void ratio as the design gradation of the asphalt, and then exerts the best noise reduction performance of the asphalt according to the proposed oil film thickness. The preparation method can also obtain an asphalt mixture that takes into account anti-skid performance, anti-cracking performance and durability when preparing asphalt according to the design gradation in the subsequent preparation, thereby solving the problem that the existing asphalt has a single performance and is difficult to have both noise reduction performance and other performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 The three gradation curves of coarse aggregate, fine aggregate and medium aggregate in Example A;

[0045] Figure 2 is a curve chart of the oil-rock ratio range determined by the leakage loss and scattering loss test in Example B;

[0046] Figure 3 is a curve diagram of the oil-rock ratio range determined by the leakage loss and scattering loss test in Example D;

[0047] Figure 4 is a curve chart of the oil-rock ratio range determined by the leakage loss and scattering loss test in Example E;

[0048] Figure 5 is a curve diagram of the oil-rock ratio range determined by the leakage loss and scattering loss test in Example F;

[0049] Figure 6 is a curve diagram of the oil-rock ratio range determined by the leakage loss and scattering loss test in Example G;

[0050] Figure 7 It is a curve chart of the oil-rock ratio range determined by the leakage loss and scattering loss test in Example H. DETAILED DESCRIPTION

[0051] In order to facilitate the understanding of the present invention, the present invention is described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0052] A method for designing an asphalt mixture comprises the following steps:

[0053] (1) Select skeleton-void diabase as the stone material, and the particle size distribution range of the stone material is at least two levels of 0-n1 and n2-n3;

[0054] 0<n1≤3≤n2<n3≤14mm, n1, n2 and n3 represent the particle size respectively;

[0055] This scheme can use two levels of ingredients, and when n1<n2, the particle size distribution is a discontinuous particle size distribution range; when n1<n2, the particle size distribution is a continuous particle size distribution range; the maximum particle size of the stone does not exceed 14mm;

[0056] (2) Use the other gradations other than 0-n1 in the stone as coarse aggregate; measure the synthetic compact density γ of the coarse aggregate s and synthetic wool volume relative density γ b , calculate the void ratio VCA of coarse aggregate DRC ;

[0057] VCA DRC =(1-γ s / γ b )×100%;

[0058] Coarse aggregate is mainly other gradations than 0-n1, such as n2-n3, and / or subsequent n4-n5;

[0059] (3) Take the 0-n1 grade in the stone as fine aggregate; design the amount of mineral powder to be added q p and the target porosity V of asphalt v ; The coarse aggregate, fine aggregate and mineral powder meet the following requirements:

[0060] q c +q f +q p =100%;

[0061]

[0062] q c is the mass percentage of coarse aggregate, q f is the mass percentage of fine aggregate, q p is the mass percentage of mineral powder; q a V is the empirical value of oil-stone ratio; v is the target void ratio; γ f is the apparent relative density of fine aggregate, γ p is the apparent relative density of the mineral powder; γ a is the relative density of asphalt;

[0063] Mineral powder is a commonly used raw material for asphalt. Its particle size is much smaller than that of stone. Its addition amount in this scheme is designed, that is, the amount of mineral powder q p is the set value; at the same time, the porosity V of asphalt v It is also a preset value, mainly used in step (7) to compare the actual void ratio, so as to confirm the design gradation of the stone; q ais the empirical value of the oil-stone ratio, which can be initially proposed based on engineering practice experience, for example, 5.5%; γf, γ p and γ a It can be directly measured by a well-known density determination experiment;

[0064] (4) Calculate the ratio of coarse aggregate to fine aggregate as q c :qf;

[0065] After step (3), q can be directly calculated c and qf, and then calculate the ratio between the two, and then reconfigure the coarse aggregate and fine aggregate according to the ratio;

[0066] (5) q calculated according to step (4) c : qf is made into medium aggregate; based on the particle size distribution range of the medium aggregate, the passing rate of the sieve hole z is increased to obtain new fine aggregate, and the passing rate of the sieve hole z is reduced to obtain new coarse aggregate; 0<z<n1;

[0067] This scheme takes into account the effect of aggregates absorbing asphalt and the interference of fine aggregates and mortar on coarse aggregates, which will cause the actual void ratio of the formed asphalt mixture to deviate from the designed void ratio. For this reason, the gradation calculated by the ratio of coarse aggregate to fine aggregate is used as the reference gradation (medium gradation); the gradation calculated by the ratio of coarse aggregate to fine aggregate is used to make the medium aggregate, and the coarse and fine gradation curves are obtained by increasing or decreasing the pass rate of the key sieve hole; for example, the pass rate of the 2.36mm key sieve hole is adjusted by ±3% to obtain the coarse and fine gradation curves, such as Figure 1 The above-mentioned “±3%” can be set as needed and is not necessarily 3%. For example, it can be ±5%, ±4%, ±2%…

[0068] After the coarse aggregate and the fine aggregate are configured in proportion, the medium aggregate can be obtained. Based on the particle size distribution range of the medium aggregate, the percentage of particles in the particle size distribution range passing through the sieve hole z is increased, that is, more fine particles pass through the sieve hole z, thereby forming fine aggregate; the percentage of particles in the particle size distribution range passing through the sieve hole z is reduced, that is, more coarse particles are located on the sieve of the sieve hole z, thereby forming coarse aggregate; thus, three gradations of coarse aggregate, fine aggregate and medium aggregate are formed; and the percentage of increasing or decreasing the passing rate can be ±3%, or other values;

[0069] (6) Determine the oil film thickness h, calculate the aggregate specific surface area A of the new fine aggregate, new coarse aggregate and medium aggregate of the corresponding gradation, and then calculate the asphalt dosage P of medium aggregate, fine aggregate and coarse aggregate respectively by the following formula: b :

[0070] Asphalt dosage P b = oil film thickness h × aggregate specific surface area A;

[0071] Asphalt with different performance requirements requires different oil film thickness h, so as to ensure that the asphalt mixture can achieve the best performance at this thickness; for example, for noise reduction asphalt, the design expectation for small-particle and large-void asphalt mixture is a higher oil film thickness to increase the elastic effect of the pavement and thus improve the noise reduction ability. Therefore, based on the general oil film thickness of 12-14μm, this scheme can initially propose a higher standard oil film thickness, which can be 16μm.

[0072] The specific surface area of ​​aggregates can be calculated by known specific surface test methods, such as the continuous flow method and the static volumetric method, or calculated according to the empirical formula of the staff;

[0073] (7) The asphalt dosage P corresponding to the medium aggregate, fine aggregate and coarse aggregate b Calculate the oil-stone ratio of each, calculate the actual porosity of each by volume method according to the oil-stone ratio of each, and compare the actual porosity with the porosity V designed in step (3) v By comparison, the medium aggregate, fine aggregate or coarse aggregate with the closest void ratio is selected as the design gradation of asphalt mixture;

[0074] The amount of oil stone Pa can be calculated by a known method.

[0075] In the formula, Pb is the asphalt dosage, that is, the percentage of asphalt mass in the total mass of asphalt mixture; Pa is the oil-stone ratio, that is, the percentage of asphalt mass in the total mass of stone.

[0076] Likewise, the calculation of the actual void fraction is also known:

[0077] Where W is the void ratio of the specimen; γ f is the relative density of the specimen’s gross volume; t is the theoretical relative density; gross volume relative density γ f Testing using the volumetric method:

[0078]

[0079] In the formula, ρ s is the gross volume density of the specimen; ρ ω The density of water at 25°C is 0.9971 g / cm 3 ;m a is the measured dry mass of the specimen; V is the measured volume of the specimen.

[0080] (8) Obtain the designed gradation for preparing the asphalt mixture according to step (7).

[0081] When the actual void ratio is compared with the void ratio V designed in step (3), vIn contrast, when the actual void ratio is close to the void ratio V designed at the beginning v When the asphalt is used, the medium aggregate, fine aggregate or coarse aggregate corresponding to the closest actual void ratio can be used as the design gradation of asphalt to ensure that the final void ratio of asphalt is controllable.

[0082] The present invention provides a method for designing asphalt mixtures, which controls the maximum aggregate size during the preparation process, separates the noise reduction capability of the asphalt mixture from the coarse aggregate and the fine aggregate, obtains the aggregate closest to the designed target void ratio as the design gradation of asphalt, and then exerts the best noise reduction performance of asphalt according to the proposed oil film thickness. The preparation method can also obtain an asphalt mixture that takes into account anti-skid performance, anti-cracking performance and durability when preparing asphalt according to the designed gradation in the subsequent preparation, thereby solving the problem that the existing asphalt has a single performance and is difficult to combine noise reduction performance and other performances.

[0083] It can be optimized that between step (7) and step (8), the oil-rock ratio range is determined according to the leakage loss and scattering loss tests, the oil-rock ratio corresponding to the intersection of the inflection point tangent of the leakage loss curve is the maximum oil-rock ratio, the oil-rock ratio corresponding to the intersection of the inflection point tangent of the scattering loss curve is the minimum oil-rock ratio, the minimum oil-rock ratio and the maximum oil-rock ratio form an optional oil-rock ratio range, the oil-rock ratio is selected within the optional oil-rock ratio range and asphalt is prepared according to the design grade, and the designed oil-rock ratio is selected according to the porosity of the asphalt;

[0084] The leakage loss and scattering loss tests are based on T0732 and T0733 of "JTG E20-2011 Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering".

[0085] In the step (8), the designed gradation and designed asphalt-to-stone ratio for preparing the asphalt mixture are obtained.

[0086] This scheme can also further optimize the oil-to-stone ratio, which refers to the percentage of the mass ratio of asphalt to mineral powder in asphalt concrete, and is one of the indicators of asphalt dosage. According to common knowledge, the amount of oil-to-stone ratio directly affects the quality of the road surface. A large oil-to-stone ratio makes the road surface prone to oil spilling, and vice versa, it affects the strength and waterproofing effect. Therefore, this scheme needs to further select the optimal oil-to-stone ratio to ensure that waterproofness, strength, anti-skid performance, crack resistance and durability can be achieved at the same time; in this regard, this scheme determines the oil-to-stone ratio range based on the leakage loss and scattering loss tests, and can determine the minimum oil-to-stone ratio and the maximum oil-to-stone ratio, and form an optional oil-to-stone ratio range between the minimum oil-to-stone ratio and the maximum oil-to-stone ratio; this scheme only needs to conduct limited experiments within the optional oil-to-stone ratio range to determine the optimal oil-to-stone ratio, which can reduce the number of repeated experiments and produce asphalt faster.

[0087] Preferably, before step (1), the properties of the asphalt are associated with the particle size range of the stone, and parameter requirements are set for particles in each particle size range;

[0088] In the step (1), when selecting stones, the particles corresponding to the selected stones in different particle size ranges are compared with the parameter requirements to ensure that the particles meet the parameter requirements.

[0089] The preparation method of this scheme compares the particles corresponding to different particle size ranges of stones with the parameter requirements when selecting materials as needed, so that the asphalt will have the necessary properties such as water resistance, strength, anti-skid performance, crack resistance and durability. Because this scheme can first limit the maximum particle size when selecting materials, and identify particles in different particle size ranges as technical indicators, it can meet different parameters at the same time, and the final comprehensive performance of the asphalt can be close to the optimal value; therefore, before step (1), the standard identification has been carried out according to the different particle size ranges of stones in the existing asphalt formula; when selecting stones in step (1), the parameter values ​​achieved by the different particle size ranges of stones are compared with the parameter requirements, which are used as the standard for material selection.

[0090] It can be optimized that in the step (1), when selecting stones, the parameter requirements of the coarse aggregate and the fine aggregate of the stones are compared respectively;

[0091] The parameters required for the comparison of coarse aggregate include: polishing value, crushing value, Los Angeles abrasion value, water absorption rate, needle-like particle content, mud content, weak particle content and one or more of the following: adhesion to modified asphalt;

[0092] The parameter requirements for comparing fine aggregate include one or more of: solidity, sand equivalent and apparent relative density.

[0093] Regarding the selection of stone materials, this plan specifically identifies the technical indicators of coarse aggregate and fine aggregate respectively. Because 0-n1 actually contains particles with a particle size of z-n1, different technical indicators are identified for coarse aggregate and fine aggregate respectively. This can ensure that both coarse aggregate and fine aggregate can be identified in a targeted manner using the same standard, and the identification results will not be affected by the large difference in 0-n1, thereby improving the accuracy of material selection to approach the optimal performance.

[0094] It can be optimized that in the step (1): when selecting stones, the particle size distribution range of the stones is 0-n1, n2-n3 and n4-n5; 0<n1≤3≤n2<n3≤n4<n5≤14mm; n3, n4 and n5 represent the particle size respectively;

[0095] In step (2), the particles n2-n3 and the particles n4-n5 are mixed in a specific ratio, and then the synthetic compact density γ of the coarse aggregate is measured. s and synthetic wool volume relative density γb .

[0096] This scheme can also use three-level grading of 0-n1, n2-n3 and n4-n5. When n3=n4, it is a continuous distribution particle size range, and when n3<n4, it is a discontinuous distribution particle size range. In order to facilitate the calculation of the synthetic compact density γ s and synthetic wool volume relative density γ b For the three-grade gradation, particles n2-n3 and particles n4-n5 are mixed in a specific ratio, which is used as the mass percentage of coarse aggregate q c ; For example, 3:1, 2:1, 1:1, etc.

[0097] It can be optimized that in step (1), n1 is 3 mm; the maximum particle size of the stone is less than 13.2 mm; the sieve hole diameter z is 2.36 mm;

[0098] In the step (6), the thickness of the oil film is set to be 15-17 μm.

[0099] This scheme uses skeleton-void diabase as stone. Its structural feature is that the skeleton is formed by stone embedding and internal friction resistance, and there will be a large number of voids inside the skeleton, and the maximum particle size of the diabase is limited to less than 13.2mm; n1 is 3mm; the sieve hole diameter z is 2.36mm. This material selection can retain a large void ratio while reducing the mixture particle size. Combined with increasing the mixture oil film thickness, this parameter can improve the noise reduction effect of asphalt.

[0100] It can be further optimized that the particle size distribution range of the diabase is a two-grade distribution of 0-3mm and 3-5mm, or a three-grade distribution of 0-3mm, 3-5mm and 5-8mm, or a two-grade distribution of 0-3mm and 5-10mm.

[0101] This scheme preferably selects materials according to the particle size distribution range of diabase as mentioned above, and the final noise reduction effect of asphalt is optimal. After determining the gradation composition and oil-stone ratio of the mixture, the anti-skid performance, anti-cracking performance and durability of the mixture are combined, and the asphalt meets the preset performance indicators.

[0102] A method for preparing noise-reducing asphalt, using the above-mentioned method for designing an asphalt mixture, preparing an asphalt mixture according to the design result of step (8); in one embodiment, the asphalt mixture is prepared according to the design gradation of step (8) and the asphalt-stone ratio determined by experience. In one embodiment, the asphalt mixture is prepared according to the design gradation and the design asphalt-stone ratio of step (8).

[0103] A noise reduction asphalt, comprising: an asphalt mixture;

[0104] The asphalt mixture is prepared by the above-mentioned method for preparing noise-reducing asphalt.

[0105] Steps (1) to (8) of this solution can be simply calculated manually, and in the best embodiment, they can be directly calculated by software as an algorithm, which can use the following asphalt mixture design system.

[0106] An asphalt mixture design system, used to execute the above-mentioned asphalt mixture design method, comprising: a material selection module, an aggregate calculation module, and a material calculation module;

[0107] The material selection module is used to perform the step (1);

[0108] The aggregate calculation module is used to execute steps (2)-(5);

[0109] The material calculation module is used to execute steps (6)-(8).

[0110] A use of an asphalt mixture in preparing noise-reducing asphalt, wherein the asphalt mixture is prepared by the above-mentioned design method for an asphalt mixture.

[0111] The performance tests used in this solution are:

[0112] ①Noise test:

[0113] Patent CN101532934B - a main drive wheel type pavement material accelerated loading test method and device is used to test the noise of asphalt.

[0114] ②Structural depth:

[0115] For specific test methods, see T0961 of "JTG 3450-2019 Highway Roadbed and Pavement Field Test Procedure".

[0116] ③High temperature stability:

[0117] High temperature rutting test is used for verification. According to T0703, the rutting plate specimen is formed by wheel rolling. The test temperature is 60℃ and the wheel pressure is 0.7MPa. The specimen and the test mold are moved to the test bench of the wheel rutting test machine. The test wheel is in the center of the specimen, and its running direction is consistent with the rolling direction of the specimen. The test machine is started and the test wheel is moved back and forth for about 1 hour, or until the maximum deformation reaches 25mm. The deformation displacement data is recorded and its dynamic stability DS is calculated according to the following formula.

[0118]

[0119] DS is the dynamic stability of asphalt mixture, times / mm; d1 corresponds to the deformation at time t1, mm; d2 corresponds to the deformation at time t2, mm; C1 is the testing machine type coefficient, the crank-connecting rod driven loading wheel reciprocating operation mode is 1.0; C2 is the specimen coefficient, the laboratory prepared 300mm wide specimen is 1.0; N is the reciprocating rolling speed of the test wheel, usually 42 times / min.

[0120] ④Stability

[0121] The water immersion Marshall and freeze-thaw splitting tests were used for verification. The water immersion Marshall test was carried out according to T0702 to form Marshall specimens. The size of the standard Marshall specimens should meet the requirements of diameter 101.6mm±0.2mm and height 63.5mm±1.3mm. The curing conditions of the standard group of Marshall specimens were kept in a constant temperature water bath at 60℃ for 30-40min, and the curing conditions of the immersion group were kept in a constant temperature water bath at 60℃ for 48h.

[0122] The stability of the mixture is evaluated by measuring the strength ratio of the splitting damage of the mixture specimens damaged by water. Each large-void asphalt mixture is divided into a non-freeze-thaw group and a freeze-thaw group. The non-freeze-thaw group specimens are subjected to a splitting test after being placed in a water bath at 25℃±0.5℃ for no less than 2 hours; the freeze-thaw group specimens are subjected to the following conditions: the specimens are first vacuum-filled with water for 15 minutes, placed in water at normal pressure for 30 minutes, put into a plastic bag and sealed with 10ml of water and placed in a temperature-controlled box at -18℃±2℃ for 16 hours, and immediately placed in a 60℃±0.5℃ constant temperature water bath for 24 hours after being taken out. Finally, similar to the non-freeze-thaw group specimens, a splitting test is carried out after being placed in a water bath at 25℃±0.5℃ for no less than 2 hours. The stability is not less than 5kN for passing.

[0123] ⑤Low temperature crack resistance

[0124] The three-point beam bending test was used for verification. The vehicle-mounted plate specimens were formed according to the test requirements and placed at room temperature for at least 12 hours to reach the test strength before demoulding. Considering the poor compaction effect at the edge of the rutting plate, a high-precision double-sided saw was used to cut the middle of the rutting plate to prepare a 250mm×30mm×35mm standard beam specimen, in which the long side of the beam was the rolling direction when the rutting plate was formed. Before loading, the beam specimen was placed in a -10℃ anhydrous ethanol water bath for no less than 1h. After the curing was completed, the specimen was quickly taken out of the environmental chamber and quickly placed on a bracket with a span of 200mm; when loading, the test machine pressure head was lowered to make it as close to the beam as possible, the loading rate was set to 50mm / min, and the device was started to apply load to the specimen until the beam broke. In order to reduce the influence of ambient temperature on the test results, the entire test process from the beam specimen leaving the environmental chamber to the completion of loading should be rapid, and the whole process should not exceed 1 minute.

[0125] If no specific techniques or conditions are specified in the following examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0126] Embodiment A:

[0127] A method for preparing noise reducing asphalt comprises the following steps:

[0128] (1) Skeleton-void diabase was selected as the stone material, and the particle size distribution range of the stone material was two-graded distribution of 0-3 mm and 3-5 mm; the details are as shown in Table 1:

[0129] Table 1 - Screening of mineral materials used and related density determination results

[0130]

[0131] (2) Take 3-5 mm as coarse aggregate; measure the synthetic compact density γ of coarse aggregate s and synthetic wool volume relative density γ b , calculate the void ratio VCA of coarse aggregate DRC ;

[0132] VCA DRC =(1-γ s / γ b )×100%;

[0133] Specifically, the synthetic compact density γ of 3-5mm diabase is tested by using a sleeve. s The determination method is to use a fixed volume of 1750cm 3 The coarse aggregate is loaded into the sleeve three times. Each time the coarse aggregate is loaded, it needs to be compacted until the coarse aggregate is flush with the sleeve mouth. The mass of the aggregate in the sleeve is weighed as M. According to the known synthetic compact density formula The synthetic compact density of 3-5 mm diabase is calculated to be γ s 1.663g / cm 3 The coarse aggregate is only 3-5mm, so its synthetic bulk relative density is γ b That is the relative bulk density of 3-5 mm stone. According to Table 1, it is 2.877 g / cm 3 ; The coarse aggregate void ratio VCA is calculated from this DRC It is 42.2%.

[0134] (3) Take the 0-n1 grade in the stone as fine aggregate; design the amount of mineral powder to be added q p The target porosity V of asphalt is 3% v 25%; the coarse aggregate, fine aggregate and mineral powder meet the following requirements:

[0135] q c +q f +q p =100%;

[0136]

[0137] q c is the mass percentage of coarse aggregate, q f is the mass percentage of fine aggregate, q p is the mass percentage of mineral powder, which is 3%; q a is the empirical value of asphalt-to-stone ratio, and the asphalt dosage q is initially estimated based on engineering practice experience. a 5.5%; V v is the target void ratio, which is 25%; γ f is the apparent relative density of fine aggregate, measured by a known method, which is 2.91 g / cm 3 ; γ p The apparent relative density of the mineral powder is 2.709 g / cm 3 ; γ a is the relative density of asphalt, is the density of high-viscosity and high-elastic modified asphalt, γ a Take 1.013g / cm 3 ;

[0138] (4) Calculate the ratio of coarse aggregate to fine aggregate as q c :qf, the result is q c :qf=89.2:7.8.

[0139] (5) q calculated according to step (4) c : qf ingredients are medium aggregate; based on the particle size distribution range of the medium aggregate, increase the 3% pass rate of the sieve hole 2.36mm to obtain new fine aggregate, and reduce the 3% pass rate of the sieve hole 2.36mm to obtain new coarse aggregate; as shown in Table 2;

[0140] Table 2 - Coarse, medium and fine aggregate gradations

[0141]

[0142] In this step (5), the passing rate of the 2.36 mm key sieve hole is adjusted by ±3% to obtain three grading curves of coarse aggregate, fine aggregate and medium aggregate, such as Figure 1 ;

[0143] (6) Determine the oil film thickness h, calculate the aggregate specific surface area A of the new fine aggregate, coarse aggregate and medium aggregate of the corresponding gradation, and then calculate the asphalt dosage P of the medium aggregate, fine aggregate and coarse aggregate respectively by the following formula b :

[0144] Asphalt dosage P b = oil film thickness h × aggregate specific surface area A;

[0145] The initial oil film thickness h is 16μm; the aggregate specific surface area can be calculated using the following empirical formula:

[0146] A=(0.41a+0.41b+0.82c+1.64d+2.87e+6.14f+12.29g+32.77h)×10 -3 ;

[0147] Wherein: a, b, c, d, e, f, g, h are the pass rates of 19 mm, 4.75 mm, 2.36 mm, 1.18 mm, 0.6 mm, 0.3 mm, 0.15 mm and 0.075 mm sieve holes respectively. The pass rates of the corresponding sieve holes can be obtained in step (1) and the unit is percentage.

[0148] Thus, the asphalt dosage of the three groups of coarse aggregate, medium aggregate and fine aggregate is calculated to be 5.0%, 5.3% and 5.7% respectively; b Substitute the oil-stone ratio The asphalt-stone ratio was calculated; and then the asphalt-stone ratios of the three groups of gradations of coarse aggregate, medium aggregate, and fine aggregate were calculated to be 5.3%, 5.7%, and 6.0%, respectively.

[0149] (7) The asphalt dosage P corresponding to the medium aggregate, fine aggregate and coarse aggregate b Calculate the oil-stone ratio accordingly, and calculate the actual porosity of each by volume method according to the oil-stone ratio;

[0150] Calculation of actual specimen void ratio:

[0151] Where W is the void ratio of the specimen; γ f is the relative density of the specimen’s gross volume; t is the theoretical relative density; gross volume relative density γ f Testing using the volumetric method:

[0152]

[0153] In the formula, ρ s is the gross volume density of the specimen; ρ ω The density of water at 25°C is 0.9971 g / cm 3 ;m a is the measured dry mass of the specimen; V is the measured volume of the specimen.

[0154] The actual void ratio is compared with the void ratio V designed in step (3) vBy comparison, the medium aggregate, fine aggregate or coarse aggregate with the closest void ratio is selected as the design gradation of asphalt mixture; the results are shown in Table 3 below;

[0155] Table 3 - Example A Synthetic Gradation Volume Index Summary Table

[0156]

[0157] It can be seen from the results in the table that the calculated void ratio of the mixture formed by the medium aggregate grading is 26.73%, which is consistent with the designed target void ratio V v The void ratio of fine aggregate gradation is 25.35%, which is close to the designed void ratio of 25%. Finally, fine aggregate is selected as the final design gradation of skeleton void type diabase (with two gradations of particle size distribution range of 0-3mm and 3-5mm).

[0158] (8) The designed gradation of the new fine aggregate in step (5) is used to prepare asphalt mixture, and the designed asphalt-aggregate ratio is 5.5%. The specific preparation steps are shown in T0702 of "JTG E20-2011 Test Procedure for Asphalt and Asphalt Mixture for Highway Engineering".

[0159] Comparative Example A1:

[0160] The basic steps for preparing the asphalt mixture in Comparative Example A1 are substantially the same as step (8) of Example A, except that Comparative Example A1 uses the gradation of the original diabase in step (1) of Example A to prepare the asphalt mixture.

[0161] Comparative Example A2:

[0162] The basic steps for preparing the asphalt mixture in Comparative Example A2 are substantially the same as step (8) of Example A, except that Comparative Example A2 uses the gradation in the middle aggregate of step (5) for preparing the asphalt mixture.

[0163] The noise test results of Example A, Comparative Example A1 and Comparative Example A2 are shown in Table 4.

[0164] Table 4 - Test results of structural depth of Example A and Comparative Example A

[0165]

[0166] illustrate:

[0167] 1. By comparing Example A with Comparative Example A1, it can be seen that the asphalt mixture of Example A adopts the design gradation of the new fine aggregate in step (5); Comparative Example A1 directly uses the most original diabase; and the final result is that the noise of Example A is 72dB, while the noise of Comparative Example A1 is 92dB. This shows that the scheme controls the maximum particle size of aggregate during the preparation process, separates the coarse aggregate and fine aggregate of the asphalt mixture and performs gradation design, obtains the aggregate closest to the designed target void ratio as the design gradation of asphalt, and then according to the proposed oil film thickness, this approach can give full play to the best noise reduction performance of asphalt.

[0168] 2. By comparing Example A with Comparative Example A2, it can be seen that the asphalt mixture of Example A adopts the designed gradation of the new fine aggregate in step (5); Comparative Example A2 uses the gradation of the medium aggregate in step (5) to prepare the asphalt mixture; and the final result is that the noise of Example A is 72dB, while the noise of Comparative Example A2 is 84dB. This shows that Comparative Example A2 does not consider the effect of aggregate absorbing asphalt and the interference of fine aggregate and mortar on coarse aggregate, which will cause the actual void ratio of the formed asphalt mixture to deviate from the designed void ratio, thereby affecting the final noise reduction performance, and thus the noise of Comparative Example A2 will be 12dB higher than that of Example A.

[0169] Embodiment B:

[0170] The basic steps of Example B are the same as those of Example A, except that, in Example B, the designed asphalt-rock ratio replaces 5.5% of step (8) in Example A; specifically,

[0171] After performing step (7) in Example A, the oil-rock ratio range is determined according to the leakage loss and scattering loss tests, the oil-rock ratio corresponding to the intersection of the inflection point tangent of the leakage loss curve is the maximum oil-rock ratio, the oil-rock ratio corresponding to the intersection of the inflection point tangent of the scattering loss curve is the minimum oil-rock ratio, and the minimum oil-rock ratio and the maximum oil-rock ratio form an optional oil-rock ratio range, such as Figure 2 ; Select an oil-stone ratio within the optional oil-stone ratio range and prepare asphalt according to the design grade; the oil-stone ratio range determined by the leakage test and the dispersion loss curve is 5.8-6.5%, and the final asphalt dosage is determined based on the maximum oil amount, which is verified and adjusted according to the void ratio of the molded mixture. The void ratio of the Marshall specimen molded at an oil-stone ratio of 6.2% is close to the design void ratio of 25%; therefore, the final oil-stone ratio of 6.2% is used as the design oil-stone ratio instead of 5.5% in step (8) of Example A.

[0172] The performance of Example B is compared with that of Example A, and the results are shown in Table 5 below.

[0173] Table 5 - Construction Depth Test Results of Examples A and B

[0174]

[0175] illustrate:

[0176] By comparing Example A with Example B, it can be seen that Example B is designed with an oil-stone ratio of 6.2% instead of 5.5% of Example A, and the structural depth of Example B is 1.25mm, while the structural depth of Example A is 1.13mm. The structural depth refers to the average depth of the open pores of the uneven road surface of a certain area, which is mainly used to evaluate the macro-roughness, drainage performance and skid resistance of the road surface. It can be seen that replacing 5.5% of Example A with 6.2% of Example B can obtain better macro-roughness, drainage performance and skid resistance. This is because the void ratio of the Marshall specimen formed by Example B is close to the designed void ratio of 25%. Based on the limited mixture particle size and the larger mixture oil film thickness, the best noise reduction effect is achieved by retaining the designed larger void ratio, so the noise reduction effect of 6.2% of Example B is the best.

[0177] Example C:

[0178] Example C is basically the same as Example B, except that Example C strictly controls the 3-5 mm coarse aggregate gradation and the 0-3 mm fine aggregate gradation, as shown in Tables 6 and 7 below.

[0179] Table 6 - Coarse Aggregate Parameter Requirements for Example C

[0180]

[0181] Table 7 - Coarse Aggregate Parameter Requirements for Example C

[0182] Inspection indicators unit Test results Design requirements Robustness (>0.3mm part) % 2.6 ≤12 Sand equivalent % 68 ≥60 Apparent relative density — 2.910 ≥2.50

[0183] Example B and Example C were subjected to noise reduction test, high temperature stability, stability and low temperature crack resistance test, and the results are shown in Table 8 below.

[0184] Table 8 - Performance Tests of Example B and Example C

[0185] project Test noise(dB) High temperature stability Stability Low temperature crack resistance Example B 70 Not passed pass Not passed Example C 72 pass pass pass

[0186] illustrate:

[0187] From the comparison between Example C and Example B, it can be seen that Example C compares the parameter requirements of coarse aggregate and fine aggregate respectively; while Example B does not compare the relevant parameter requirements of coarse aggregate and fine aggregate; and Example C has noise reduction performance, high temperature stability, stability and low temperature crack resistance at the same time; while Example B is lower in high temperature stability and low temperature crack resistance than Example C. This shows that when selecting materials, this scheme will first limit the maximum particle size, and identify particles of different particle size ranges as technical indicators, which can meet different parameters at the same time, and the final comprehensive performance of asphalt can be close to the optimal value.

[0188] Embodiment D:

[0189] The basic steps of Example D are basically the same as those of Example C, except that in step (3), the amount of mineral powder to be added is designed to be p The target porosity V of asphalt is 3% v 20%;

[0190] Embodiment E:

[0191] The basic steps of Example E are basically the same as those of Example C, except that, in step (1) of Example E, skeleton void type diabase is selected as the stone material, and the particle size distribution range of the stone material is three-graded with 0-3mm, 3-5mm, and 5-8mm; and the coarse aggregate meets the parameter requirements of Table 9 below, and the fine aggregate parameter requirements are the same as those of Example C.

[0192] Table 9 - Coarse Aggregate Parameter Requirements for Example E

[0193]

[0194]

[0195] In step (2), the coarse aggregates are 3-5 mm and 5-8 mm in two gradations and are mixed at a ratio of 3:1; in step (3), the amount of mineral powder to be added is designed. p The target porosity V of asphalt is 3% v is 20%.

[0196] Example F:

[0197] The basic steps of Example F are basically the same as those of Example E, except that in Example F, the amount of mineral powder to be added in step (3) is designed to be q p The target porosity V of asphalt is 3% v is 25%.

[0198] Example G:

[0199] The basic steps of Example G are basically the same as those of Example C, except that, in step (1), skeleton void type diabase is selected as the stone material, and the particle size distribution range of the stone material is two-graded of 0-3 mm and 5-10 mm; and the coarse aggregate meets the parameter requirements of Table 10 below, and the fine aggregate parameter requirements are the same as those of Example C.

[0200] Table 10 - Coarse Aggregate Parameter Requirements for Example G

[0201]

[0202] In step (3), the amount of mineral powder to be added is designed as p The target porosity V of asphalt is 3% v is 20%.

[0203] Embodiment H:

[0204] The basic steps of Example H are basically the same as those of Example G, except that in Example G, the amount of mineral powder to be added in step (3) is designed to be q p The target porosity V of asphalt is 3% v is 25%.

[0205] The final design gradation and designed asphalt-rock ratio in step (8) of Example DH are shown in Table 11 below. The corresponding asphalt-rock ratio range is determined by the scattering test and the leakage test. Figure 3-Figure 7 ;

[0206] Table 11 - Design gradation and design oilstone of Example DH

[0207]

[0208] The structural depth, noise reduction effect, high temperature stability, stability and low temperature crack resistance test of Example DH are shown in Table 12 below.

[0209] Table 12 - Performance Tests of Example DH

[0210] Gradation type Void ratio (%) TD(mm) Test noise(dB) High temperature stability Stability Low temperature crack resistance Example D 20 1.24 75 pass pass pass Example E 20 1.56 75 pass pass pass Example F 25 1.62 71 pass pass pass Example G 20 1.85 74 pass pass pass Example H 25 1.95 69 pass pass pass

[0211] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to these embodiments without departing from the principles and intent of the present invention, and that the scope of the present invention is defined by the claims and their equivalents. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the associated listed items.

Claims

1. A method for designing an asphalt mixture, characterized in that: The following steps are involved: (1) Select skeleton-voided diabase as the stone material, and the particle size distribution range of the stone material is at least two levels of 0-n1 and n2-n3; 0<n1≤3≤n2<n3≤14mm; n1, n2 and n3 represent the particle size respectively; (2) Use the other gradations other than 0-n1 in the stone as coarse aggregate; measure the synthetic compact density γ of the coarse aggregate s and synthetic wool volume relative density γ b , calculate the void ratio VCA of coarse aggregate DRC ; VCA DRC =(1-γ s / c b )×100%; (3) Take the 0-n1 grade in the stone as fine aggregate; design the amount of mineral powder to be added q p and the target porosity V of asphalt v ; The coarse aggregate, fine aggregate and mineral powder meet the following requirements: q c +q f +q p =100%; q c is the mass percentage of coarse aggregate, q f is the mass percentage of fine aggregate, q p is the mass percentage of mineral powder; q a V is the empirical value of oil-stone ratio; v is the target void ratio; γ f is the apparent relative density of fine aggregate, γ p is the apparent relative density of the mineral powder; γ a is the relative density of asphalt; (4) Calculate the ratio of coarse aggregate to fine aggregate as q c :q f ; (5) q calculated according to step (4) c :q f Making into medium aggregate; based on the particle size distribution range of the medium aggregate, increasing the passing rate of the sieve hole z to obtain new fine aggregate, and reducing the passing rate of the sieve hole z to obtain new coarse aggregate; 0<z<n1; (6) Determine the oil film thickness h, calculate the aggregate specific surface area A of the new fine aggregate, new coarse aggregate and medium aggregate of the corresponding gradation, and then calculate the asphalt dosage P of medium aggregate, fine aggregate and coarse aggregate respectively by the following formula: b : Asphalt dosage P b = oil film thickness h × aggregate specific surface area A; (7) The asphalt dosage P corresponding to the medium aggregate, fine aggregate and coarse aggregate b Calculate the oil-stone ratio of each, calculate the actual porosity of each by volume method according to the oil-stone ratio of each, and compare the actual porosity with the porosity V designed in step (3) v By comparison, the medium aggregate, fine aggregate or coarse aggregate with the closest void ratio is selected as the design gradation of asphalt mixture; (8) Obtain the designed gradation for preparing the asphalt mixture according to step (7).

2. The method for designing an asphalt mixture according to claim 1, characterized in that: Prior to step (1), the properties of the asphalt are associated with the particle size range of the stone, and parameter requirements are set for particles in each particle size range; In the step (1), when selecting stones, the particles corresponding to the selected stones in different particle size ranges are compared with the parameter requirements to ensure that the particles meet the parameter requirements.

3. The method for designing an asphalt mixture according to claim 2, characterized in that: In the step (1), when selecting stones, the parameter requirements of the coarse aggregate and the fine aggregate of the stones are compared respectively; The parameters required for the comparison of coarse aggregate include: polishing value, crushing value, Los Angeles abrasion value, water absorption rate, needle-like particle content, mud content, weak particle content and one or more of the following: adhesion to modified asphalt; The parameter requirements for comparing fine aggregate include one or more of: solidity, sand equivalent and apparent relative density.

4. The method for designing an asphalt mixture according to claim 1, characterized in that: In the step (1): when selecting stones, the particle size distribution range of the stones is 0-n1, n2-n3 and n4-n5; 0<n1≤3≤n2<n3≤n4<n5≤14mm; n3, n4 and n5 represent the particle size respectively; In step (2), the particles n2-n3 and the particles n4-n5 are mixed in a specific ratio, and then the synthetic compact density γ of the coarse aggregate is measured. s and synthetic wool volume relative density γ b .

5. A method for designing an asphalt mixture according to claim 1 or 4, characterized in that: The particle size distribution range of diabase is two-grade distribution of 0-3mm and 3-5mm, or three-grade distribution of 0-3mm, 3-5mm and 5-8mm, or two-grade distribution of 0-3mm and 5-10mm; In the step (1), n1 is 3 mm; the maximum particle size of the stone is less than 13.2 mm; and the sieve hole diameter z is 2.36 mm; In the step (6), the thickness of the oil film is set to be 15-17 μm.

6. A method for designing an asphalt mixture according to any one of claims 1 to 4, characterized in that: Between step (7) and step (8), the oil-rock ratio range is determined according to the leakage loss and scattering loss tests, the oil-rock ratio corresponding to the intersection of the inflection point tangent of the leakage loss curve is the maximum oil-rock ratio, the oil-rock ratio corresponding to the intersection of the inflection point tangent of the scattering loss curve is the minimum oil-rock ratio, the minimum oil-rock ratio and the maximum oil-rock ratio form an optional oil-rock ratio range, the oil-rock ratio is selected within the optional oil-rock ratio range and asphalt is prepared according to the design grade, and the design oil-rock ratio is selected according to the porosity of the asphalt; In the step (8), the designed gradation and designed asphalt-to-stone ratio for preparing the asphalt mixture are obtained.

7. A method for preparing noise-reducing asphalt, using the asphalt mixture design method according to any one of claims 1 to 6, characterized in that: Asphalt mixture is prepared according to the design result of step (8).

8. A noise reduction asphalt, characterized in that: include: Asphalt mixture; The asphalt mixture is prepared by the method for preparing noise-reducing asphalt according to claim 7.

9. A design system for asphalt mixture, characterized in that: A method for designing an asphalt mixture according to any one of claims 1 to 6, comprising: a material selection module, an aggregate calculation module, and a material calculation module; The material selection module is used to perform the step (1); The aggregate calculation module is used to execute steps (2)-(5); The material calculation module is used to execute steps (6)-(8).

10. Use of an asphalt mixture in preparing noise-reducing asphalt, characterized in that: The designed gradation and designed asphalt-aggregate ratio of the asphalt mixture are designed according to the asphalt mixture design method described in claim 7.

Citation Information

Patent Citations

  • A method and apparatus for accelerated loading testing of main drive wheel road surface materials

    CN101532934B

  • Method for designing dense-graded rubber asphalt mixture based on asphalt film thickness

    CN104609774A

  • Gradation method of small-grain-size skeleton dense type asphalt mixture

    CN106544944A

  • Fine grain type semi-open graded asphalt mixture and mix proportion design method thereof

    CN111153632A

  • Anti-rutting drainage ultrathin overlay asphalt mixture and preparation method thereof

    CN111423156A

Cited By

  • Mute asphalt mixture and design method thereof

    CN121122512A